KINERJA PERAWAT DALAM IMPLEMENTASI PENCEGAHAN FLEBITIS PADA PASIEN RAWAT INAP DI RS YOS SUDARSO PADANG TAHUN 2024 - elizaliza elizajupri; ElizaEliza elizajupri; ElizaEliza elizajupri (PT Nuansa Fajar Cemerlang, 2026)
Introduction: Phlebitis is one of the nosocomial infections that remains a significant issue in healthcare services. Data from the World Health Organization (WHO) in 2022 reported that the incidence of phlebitis reached 5% per year. In government hospitals in Indonesia, the incidence rate is reported to be as high as 50.1%. At Yos Sudarso Hospital Padang, phlebitis cases fluctuated, with an incidence of 0.5% in December 2021, remaining at 0.5% in December 2022, and increasing to 0.55% in June 2023 and 0.46% in November 2023, while the target is 0%. This study aimed to describe nurses’ performance in implementing phlebitis prevention in the inpatient ward of Yos Sudarso Hospital Padang in 2024. Methods: This study used a descriptive design conducted from March to October 2024. The population consisted of all nurses working in the inpatient ward of Yos Sudarso Hospital Padang, totaling 53 respondents. A total sampling technique was applied, where all population members were included as samples. Data were collected using a questionnaire and analyzed using univariate analysis, presented in frequency distribution tables. Results: The results showed that 32.1% of respondents had poor performance in implementing phlebitis prevention, while the majority demonstrated good performance. Discussion: Although most nurses showed good performance, a proportion still demonstrated suboptimal performance in phlebitis prevention. This indicates the need for improved supervision and management. It is recommended that team leaders collaborate with head nurses to supervise healthcare workers, particularly in intravenous therapy procedures, to reduce the incidence of phlebitis